2020
DOI: 10.1002/cbm.2176
|View full text |Cite
|
Sign up to set email alerts
|

Assessing alexithymia in forensic settings: Psychometric properties of the 20‐item Toronto Alexithymia Scale among incarcerated adult offenders

Abstract: Background Alexithymia is a trait involving difficulty identifying feelings (DIF), difficulty describing feelings (DDF) and externally orientated thinking (EOT). It is a risk factor for criminal behaviour. It is commonly assessed with the Toronto Alexithymia Scale (TAS‐20), but the psychometrics of the TAS‐20 have not been tested across the range of offender populations, and it has been suggested it might be unsuitable in incarcerated offenders. Aim To establish the psychometrics of the TAS‐20 among incarcerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
(69 reference statements)
0
2
0
Order By: Relevance
“…A model that—in addition to the basic three-dimensional structure—introduced a nested method factor that captures that method-specific variance associated with the reverse item wording yielded a significant improvement in model fit (see Table 1 ). In the psychometric literature on the TAS-20, it has been reported that such a method factor model might be superior to other models ( Meganck et al, 2008 ; Preece et al, 2021 ; for a more critical evaluation, see Gignac et al, 2007 ). However, taking a closer look at the loading pattern, we noticed that all negatively keyed EOT items loaded higher on their method factor than on the actual content factor.…”
Section: Resultsmentioning
confidence: 99%
“…A model that—in addition to the basic three-dimensional structure—introduced a nested method factor that captures that method-specific variance associated with the reverse item wording yielded a significant improvement in model fit (see Table 1 ). In the psychometric literature on the TAS-20, it has been reported that such a method factor model might be superior to other models ( Meganck et al, 2008 ; Preece et al, 2021 ; for a more critical evaluation, see Gignac et al, 2007 ). However, taking a closer look at the loading pattern, we noticed that all negatively keyed EOT items loaded higher on their method factor than on the actual content factor.…”
Section: Resultsmentioning
confidence: 99%
“…Despite this, reviews have shown that it is common in the literature for studies to report a lower alpha coefficient for the EOT subscale ( 55 ). Pertinent to this sample, and subsequent to the conduct of the current study, the EOT subscale has recently been found to have an unacceptable alpha coefficient within an offender population ( 56 ).…”
Section: Methodsmentioning
confidence: 88%